POPULASI AYAT-AYAT MAHABBAH DALAM AL-QUR’AN: SATU ANALISIS AWAL - Khosim, Norullisza; Abd Samad, Mohd Shamsul Hakim (Jurnal ’Ulwan, 2024)
Mahabbah is a gift of feelings from Allah SWT to each of His servants. The true nature of mahabbah needs to be understood properly so that this feeling is not misjudged and driven to things that are not allowed by the Sharia. Understanding of mahabbah can be done by knowing the population of the word mahabbah used in the Qur’an. Thus, this study aims to identify the population of mahabbah verses found in the Qur’an, then the data will be analyzed to determine the use of the words and the frequency of repetition of those words, as well as the division of mahabbah, for the purpose of real understanding and management according to the Qur’anic perspective. This study uses a document review approach as a data collection method by applying content analysis methods as data analysis. The results show that the existence of the word mahabbah in the Qur’an in large numbers and in various forms has led to its true meaning for human life and guidance for a person to manage such feelings towards reaching the peak of mahabbah as outlined by the Sharia.